PARTISIPASI MASYARAKAT DALAM MENGAWASI PROGRAM ANGGARAN DANA DESA DI DESA DUAI DISTRIK BRUYADORI KABUPATEN BIAK NUMFOR - KORWA, JIMMY CARROLUS (JURNAL ADMINISTRASI PUBLIK, 2020)
Community participation is a spontaneous action carried out by the community individually to engage with others in the activities carried out, both physical and non-physical activities, which are carried out to achieve certain goals, while one of them is about the ADD program in order to effectively run the ADD management. involved to oversee the village fund budget program that is used so that it is right on target for the welfare of the community. This research is a research with a qualitative approach. Data collection techniques in this study used the method of observation that is direct observation of the research location and conducting interviews and documentation. The purpose of this study is to find out how community participation in overseeing the Village Fund Budget Program. Community participation in the distribution of information, empowerment, and decision making in the village of Duai is still lacking and limited by the community, because in the distribution of information is still closed and not transparent, in the empowerment of the duai village government has given the empowerment budget for the community, in the decision making village government is still not open to provide space for the community to be involved in decision making.Keywords: Community Participation, Supervision, Add